Investigation in terms of digestive values, silages quality and nutrient content of the using pomegranate pomace in the ensiling of apple pomace with high moisture contents - Kanber Kara; Berrin Kocaoglu Guclu; Erol Baytok; Eray Aktug; Fatma Karakas Oguz; Adem Kamalak; Ali Ihsan Atalay (Journal of Applied Animal Research, 2018)
The purpose of present study was to determine the quality and in vitro digestion parameters in silages of 100% pomegranate pomace (PPS), 100% apple pomace (APS) and 50% pomegranate pomace + 50% apple pomace (PAPS). The digestion parameters of 10% or 20% using of these silages in total mix ration (TMR) of dairy cattle were researched. The dry matter (DM), crude protein, flavonoids, tannins and anthocyanins of pomegranate pomace were higher than those of apple pomace. Fibrous and non-fibrous carbohydrates of pomegranate pomace were similar to those of apple pomace. The silage DM losses in APS decreased with pomegranate pomace (p = .004). The silage density, gas-methane production, and estimated digestion values of PPS and PAPS were higher than those of APS (p < .05). Lactic acid and pH value of APS and the PAPS were higher than the PPS (p < .01). The using of PPS up to 20% in TMR decreased in vitro estimated digestion of TMR (p < .05). The using of APS or PAPS up to 20% in TMR was appropriate for in vitro results. As a result, ensilaging of apple pomace with pomegranate pomace can increase silage density, silage DM; and can decrease silage DM losses; and do not affect silage quality-digestion parameters.